The catfish genus Erethistoides (Siluriformes: Sisoridae) in Myanmar, with descriptions of three new species - Ng, Heok Hee; Ferraris, Jr., Carl J.; Neely, David A. (Zootaxa, 2012)
The presence of the sisorid catfish genus Erethistoides in Myanmar, represented by three new species, is recorded for thefirst time. This discovery from the Irrawaddy and Sittang river drainages from central Myanmar and the Ann ChaungRiver drainage in western Myanmar extends the documented range of the genus beyond the Ganges/Brahmaputra Riverbasin. Erethistoides longispinis is distinguished from congeners in having the following unique combination ofcharacters: length of the dorsal-fin spine 24–27% SL, length of the pectoral-fin spine 29–35% SL, and absence ofproximally-directed serrations on the anterior edge of the pectoral spine. Erethistoides luteolus differs from congeners inhaving the following combination of characters: yellow base color of the body, body with distinct bands, vertebrae 30,premaxillary tooth band partially exposed when the mouth is closed, length of the dorsal-fin spine 14–15% SL, length ofthe pectoral-fin spine 21–24% SL, absence of proximally-directed serrations on the anterior edge of the pectoral spine,length of the adipose-fin base 16–17% SL, length of the caudal peduncle 22–25% SL and depth of the caudal peduncle 6–7% SL. Erethistoides vesculus is distinguished from congeners in having the following combination of characters: creambase color of the body, body with distinct bands, vertebrae 30, premaxillary tooth band partially exposed when the mouthis closed, length of the dorsal-fin spine 15% SL, length of the pectoral-fin spine 22–23% SL, absence of proximally-directed serrations on the anterior edge of the pectoral spine, length of the adipose-fin base 14–15% SL, length of the caudal peduncle 19–21% SL and depth of the caudal peduncle 4–5% SL.